Long-term recovery from intimate partner violence: definitions by Australian women - Carman, Mary Jean (Journal of family violence, 2023)
This study explored the lived experience of Australian women affected by intimate partner violence (IPV) and determined whether and how recovery was part of that experience. An online survey of 665 Australian women in long-term recovery from IPV gathered qualitative information about their experiences and their definitions of recovery. The guiding methodology for data analysis was qualitative content analysis, as it provided a close analysis of the manifest meanings of the women’s responses and an interpretation of the latent themes within the data. Outcomes included a thematic analysis and the numbers of women referring to each theme. The women’s definitions focused on their lived experiences of recovery rather than on the psychological and academic constructs favoured by researchers. The five themes identified in the women’s definitions were safety and survival, gaining freedom, moving on, enjoying a better life, and issues with children and parenting. These themes did not represent sequential stages but generally occurred concurrently. Relapses, digressions, and highs and lows were also common aspects of recovery. Thus, these themes were more like threads woven together in a multi-axial continuum or recovery journey, rather than sequential phases. Although many women considered they had recovered from IPV, most women found recovery to be ongoing. Some women struggled to make any progress in recovery at all. Overall, recovery from IPV is multidimensional and individualistic in nature. It is an arduous journey that evolves over a long period of time and requires a great deal of support.